High Content Screening of a Kinase-Focused Library Reveals Compounds Broadly-Active against Dengue Viruses - Cruz, Deu John M.; Koishi, Andrea Cristine; Taniguchi, Juliana Bosso [UNESP]; Li, Xiaolan; Milan Bonotto, Rafaela; No, Joo Hwan; Kim, Keum Hyun; Baek, Sungmin; Kim, Hee Young; Windisch, Marc Peter; Pamplona Mosimann, Ana Luiza; de Borba, Luana; et al. (Public Library of Science (PLoS), 2013)
Dengue virus is a mosquito-borne flavivirus that has a large impact in global health. It is considered as one of the medically important arboviruses, and developing a preventive or therapeutic solution remains a top priority in the medical and scientific community. Drug discovery programs for potential dengue antivirals have increased dramatically over the last decade, largely in part to the introduction of high-throughput assays. In this study, we have developed an image-based dengue high-throughput/high-content assay (HT/HCA) using an innovative computer vision approach to screen a kinase-focused library for anti-dengue compounds. Using this dengue HT/HCA, we identified a group of compounds with a 4-(1-aminoethyl)-N-methylthiazol-2-amine as a common core structure that inhibits dengue viral infection in a human liver-derived cell line (Huh-7.5 cells). Compounds CND1201, CND1203 and CND1243 exhibited strong antiviral activities against all four dengue serotypes. Plaque reduction and time-of-addition assays suggests that these compounds interfere with the late stage of viral infection cycle. These findings demonstrate that our image-based dengue HT/HCA is a reliable tool that can be used to screen various chemical libraries for potential dengue antiviral candidates. © 2013 Cruz et al.
Keywords: alpha2a interferon; chloroquine; phosphotransferase inhibitor; ribavirin; affinity chromatography; animal cell; antiviral activity; Chikungunya alphavirus; computer model; computer program; controlled study; Dengue virus; dose response; drug structure; genotype; high throughput screening; human; human cell; nonhuman; nucleotide sequence; peptide library; validation process; viral disease immunofluorescence assay; Antiviral Agents; Cell Line; Dengue Virus; Drug Discovery; Hepatocytes; High-Throughput Screening Assays; Humans; Microbial Sensitivity Tests